Interrelation of psychophysiological indicators and physical readiness of qualified wrestlers - Tropin, Y.; Boychenko, N. (Slobozhanskyi herald of science and sport, 2018)
Purpose: to establish the features and degree of interrelation of psychophysiological indicators and physical readiness among qualified wrestlers.